1999
DOI: 10.1111/j.1528-1157.1999.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Death in Patients with Intractable Epilepsy During Nitrazepam Treatment

Abstract: Summary:Purpose: Increased risk of death has been reported in patients with intractable epilepsy (IE) taking nitrazepam (NZP).Methods: Between January 1983 and March 1994, 302 patients with IE were entered into a NZP compassionate-plea protocol. NZP was discontinued if there was 4 0 % seizure reduction or significant side effects. In some patients with >SO% reduction, it also was discontinued for lack of sufficient effect. At the end of follow-up for this study, 62 patients remained taking NZP. Patients took N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…If cohorts were (Kurtz et al, 1998(Kurtz et al, ) (1958 E, S&W FU of birth cohort 124 2,396 0.0623 Cutfield (Cutfield & Wrightson, 1987) (1961 New Zealand Surgery for TLE 26 295 0.0237 Wakamoto (Wakamoto et al, 2000(Wakamoto et al, ) (1961 Japan Childhood-onset epilepsy 155 2,872.1 0.282 Brorson (Brorson & Wranne, 1987) (1964 Sweden Children with active epilepsy 194 2,328 0.224 Vining (Vining et al, 1997(Vining et al, ) (1968 U.S.A. Hemispherectomy in children 58 341 0.0135 Davies (Davies & Weeks, 1993) (1969 Wales Epilepsy surgery patients 58 348 0.0252 Verity (Verity et al, 1992(Verity et al, ) (1970 United Kingdom Children with ‡1 afebrile seizure 84 491.4 0 Nashef (Nashef et al, 1995a(Nashef et al, ) (1970 England Residential school 310 4,135 0.201 Klenerman (Klenerman et al, 1993(Klenerman et al, ) (1980 England Epilepsy institution 3,392 0.422 Udani (Udani et al, 1993(Udani et al, ) (1980 India Children difficult to control epilepsy 100 153.75 0.00714 Cohen (Cohen et al, 1995(Cohen et al, ) (1981 U.S.A. Surgery cavernous malformations 51 249.21 0.0267 Rintahaka (Rintahaka et al, 1999(Rintahaka et al, ) (1983 U.S.A. Compassionate use of nitrazepam 294 1,560 0.00714 Shinnar (Shinnar et al, 2005) (1983) U.S.A. Children with 1st unprovoked seizure 407 5,779.4 0.493 Lindsten (Lindsten et al, 2000(Lindsten et al, ) (1985 Sweden Adults newly diagnosed seizures 107 850 0.185 Jonas (Jonas et al, 2004(Jonas et al, ) (1986 U.S.A. Hemispherectomy in children 115 408.5 0.00233 Callenbach (Callenbach et al, 2001(Callenbach et al, ) (1988 The Netherlands Children newly diagnosed seizures 472 2,340 0.0675 Uthman (Uthman et al, 2004(Uthman et al, ) (1989 U.S.A. Vagal nerve stimulation 48 153.6 0.0218 Nashef (Nashef et al, 1995b)…”
Section: Resultsmentioning
confidence: 99%
“…If cohorts were (Kurtz et al, 1998(Kurtz et al, ) (1958 E, S&W FU of birth cohort 124 2,396 0.0623 Cutfield (Cutfield & Wrightson, 1987) (1961 New Zealand Surgery for TLE 26 295 0.0237 Wakamoto (Wakamoto et al, 2000(Wakamoto et al, ) (1961 Japan Childhood-onset epilepsy 155 2,872.1 0.282 Brorson (Brorson & Wranne, 1987) (1964 Sweden Children with active epilepsy 194 2,328 0.224 Vining (Vining et al, 1997(Vining et al, ) (1968 U.S.A. Hemispherectomy in children 58 341 0.0135 Davies (Davies & Weeks, 1993) (1969 Wales Epilepsy surgery patients 58 348 0.0252 Verity (Verity et al, 1992(Verity et al, ) (1970 United Kingdom Children with ‡1 afebrile seizure 84 491.4 0 Nashef (Nashef et al, 1995a(Nashef et al, ) (1970 England Residential school 310 4,135 0.201 Klenerman (Klenerman et al, 1993(Klenerman et al, ) (1980 England Epilepsy institution 3,392 0.422 Udani (Udani et al, 1993(Udani et al, ) (1980 India Children difficult to control epilepsy 100 153.75 0.00714 Cohen (Cohen et al, 1995(Cohen et al, ) (1981 U.S.A. Surgery cavernous malformations 51 249.21 0.0267 Rintahaka (Rintahaka et al, 1999(Rintahaka et al, ) (1983 U.S.A. Compassionate use of nitrazepam 294 1,560 0.00714 Shinnar (Shinnar et al, 2005) (1983) U.S.A. Children with 1st unprovoked seizure 407 5,779.4 0.493 Lindsten (Lindsten et al, 2000(Lindsten et al, ) (1985 Sweden Adults newly diagnosed seizures 107 850 0.185 Jonas (Jonas et al, 2004(Jonas et al, ) (1986 U.S.A. Hemispherectomy in children 115 408.5 0.00233 Callenbach (Callenbach et al, 2001(Callenbach et al, ) (1988 The Netherlands Children newly diagnosed seizures 472 2,340 0.0675 Uthman (Uthman et al, 2004(Uthman et al, ) (1989 U.S.A. Vagal nerve stimulation 48 153.6 0.0218 Nashef (Nashef et al, 1995b)…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we concluded that nitrazepam may be an effective adjunctive antiepileptic drug for patients with infantile spasms, which did not respond sufficiently to topiramate. Rintahaka et al 28 reported a higher mortality rate in children with epilepsy taking nitrazepam in comparison with children with epilepsy who did not take nitrazepam. The adverse effects were usually dose related and decreased with dose reduction.…”
Section: Discussionmentioning
confidence: 98%
“…The potential utility of these AEDs is further compromised by their respective side effect profiles; whereas benzodiazepines often produce significant sedation, valproate and felbamate pose a noteworthy—albeit very small—risk of fatal hepatotoxicity. Similarly, nitrazepam was associated with rather high mortality among infants participating in a compassionate use study . Risk–benefit assessment is especially challenging for these agents, and most parents would certainly balk at the possibility of any potentially lethal side effect in the absence of ongoing seizures.…”
Section: Discussionmentioning
confidence: 99%